SENSES AND “SENSUAL DATA” - Półtawski, Andrzej (Studia Philosophiae Christianae, 2020)
One of the main goals of modern philosophy was to achieve an in-depth insight into the foundations of empirical knowledge. The problem was expected to be resolved by the analysis of experience. However, the road to a plausible account of experience was at the very beginning obstructed by turning the analysis into a search for clear and distinctive elements of experience and by sticking to purely intellectual intuition as means of this analysis. Moreover, clear and distinctive elements of experience were thought of as the basis of cognitive certainty. Both psychology and philosophy, at least until the nineteen-thirties, were deeply influenced by this essentially rationalistic conception of sensor experience. It is gestalt psychology and phenomenology that should be merited for overcoming that ill-conceived model. Only by taking into account the immediate sensor relation between the human subject and the environment, it is possible to show the kind of unity which is the prerequisite of human intellect.